Childhood emotional but not physical or sexual maltreatment predicts prosocial behavior in late adolescence: A daily diary study. (May 2023) - Kong, Feng; Zhu, Ningzhe; Ye, Ying; Li, Chengcheng; Zhang, Linting; Li, Wenjie
Abstract: Background: Childhood maltreatment (CM), including physical, emotional, and sexual maltreatment, is detrimental to adolescents' psychological and behavioral outcomes. However, most studies on the relationship between CM and prosocial behavior focused on the overall experience of CM. Since different forms of CM exert various influences on adolescents, it is essential to find out which form of CM has the strongest link with prosocial behavior and the underlying mechanism behind it to fully understand this relationship and design a specific intervention for promoting prosocial behavior. Objective: Guided by internal working model theory and hopelessness theory, this study aimed to investigate the connections of multiple forms of CM with prosocial behavior, and explore the mediating mechanism of gratitude from the perspective of the broaden-and-build theory through a 14-day daily diary study. Participants: A total of 240 Chinese late adolescents (217 females; M age = 19.02, SD age = 1.83) from a college volunteered for this study and completed questionnaires regarding CM, gratitude, and prosocial behavior. Methods: A multilevel regression analysis was conducted to investigate which form of CM was correlated to prosocial behavior, and a multilevel mediation analysis was applied to examine the underlying mechanism (i.e., gratitude) behind this relationship. Results: The results of the multilevel regression analysis showed that it was childhood emotional maltreatment, but not physical or sexual maltreatment that negatively predicted prosocial behavior. The results of the multilevel mediation analysis indicated that gratitude mediated the relationship between childhood emotional maltreatment and prosocial behavior. Conclusions: Findings from the present study highlight the predictive effect of childhood emotional maltreatment on late adolescents' prosocial behavior and the mediating role of gratitude in this link. Highlights: Childhood emotional maltreatment negatively predicted prosocial behavior in late adolescents. Childhood physical and sexual maltreatment had no predicted effects on prosocial behavior Gratitude played mediating role in the link of childhood emotional maltreatment with prosocial behavior.